Enterprise information systems : 18th International Conference, ICEIS 2016, Rome, Italy, April 25?28, 2016, Revised selected papers /: 18th International Conference, ICEIS 2016, Rome, Italy, April 25?28, 2016, Revised selected papers. (2017) - Unknown
No abstract available